Предмет: Математика, автор: soroka9046

Пожалуйста помогите с уравнением и если можете подробно объяснить.

Приложения:

Ответы

Автор ответа: NNNLLL54
1

\dfrac{1}{cos^2x}+ctg\Big(\dfrac{\pi}{2}+x\Big)=tg^2x+\dfrac{cos2x}{cos^2x}\\\\\\\Big(1+tg^2x\Big)-tgx=tg^2x+\dfrac{cos^2x-sin^2x}{cos^2x}\\\\\\1+tg^2x-tgx=tg^2x+1-tg^2x\\\\tg^2x-tgx=0\\\\tgx\cdot (tgx-1)=0\\\\a)\ \ tgx=0\ \ \to \ \ \ x=\pi n\; ,\; n\in Z\\\\b)\ \ tgx=1\ \ \to \ \ \ x=\dfrac{\pi}{4}+\pi k\ ,\ k\in Z\\\\Otvet:\ \ x=\pi n\ \ ,\ \ x=\dfrac{\pi}{4}+\pi k\ \ ,\ \ k,n\in Z\; .

Похожие вопросы